Analisis Wacana Kritis Fairclough Terhadap Representasi Ditjen Pajak dalam Tagar #PercumaBayarPajak di Twitter: Perspektif Analisis Media Sosial - Anggriyani, Vera; Mayasari, Mayasari; Rifai, Maulana (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research conducted discourse analysis using Norman Fairclough's approach to the hashtag #PercumaBayarPajak on the social media platform Twitter X with a focus on the image of the Directorate General of Taxes. The results of the textual analysis show the use of repetition, figures of speech and diction used to voice dissatisfaction with the tax system and the Directorate General of Taxes. At the level of discourse practice, research identifies the production and consumption of tweets within the hashtag movement, reflecting the active participation of Twitter X users in conveying their criticism. Analysis of sociocultural practices connects hashtags with social, institutional and social situations, showing how society unites through social media to criticize tax practices that are considered detrimental. This research concludes that #PercumaPayarPajak has become an important medium for the public to voice their dissatisfaction and criticism of the tax system, especially after the emergence of corruption cases at the Directorate General of Taxes. The implications of this research provide deep insight into how social media can be a tool for social change and public opinion regarding tax policy.